Kontribusi Pendapatan Usahatani Kopi Terhadap Pendapatan Rumah Tangga Petani Di Desa Detusoko Barat Kabupaten Ende - Jeharu, Onesimus Tricahyo Agramedha; Kapioru, Charles; Darlen, Maria Fransiska; Adar, Damianus (Buletin Ilmiah Impas, 2024)
This research aims to determine the amount of coffee farming income and the magnitude of the contribution of coffee farming to farmer household income. Data collection was carried out in West Detusoko Village, Detusoko District, Ende Regency, because it is one of the coffee producing areas. The population in this study was taken based on the number of family heads in West Detusoko Village, namely 219 people. The sample was determined using a simple random sampling method and calculated using the Slovin formula with a sample size of 69 respondents. The analytical method used in this research is a qualitative-quantitative descriptive method, income analysis and contribution analysis. The research results showed that the amount of income obtained by 69 respondents from coffee farming was IDR. 4.933.862/year/farmer. Income from rice farming is Rp. 2,135,848/planting season/farmer, so that in 1 year the farmer's income is Rp. 4,271,696/year/farmer, because they carry out two planting seasons in 1 year. Meanwhile, income outside the agricultural sector of 33 respondents who have businesses outside the agricultural sector was IDR. 973.061/year/farmer. So, the total income of farmer households is Rp. 10.178.619/year/farmer. Coffee farming contributes 48.47% to the household income of farmers.. This shows that coffee farming does not contribute significantly to farmer household income.